Pharmacological Evaluation of the Wound Healing Potential of Rubus paniculatus in Preclinical Models - Shukla, Vishal; Khan, Waseem; Singh, Sanjay (Journal of Neonatal Surgery, 2025)
Rubus paniculatus, a wild Himalayan raspberry traditionally used in Indian ethnomedicine, was evaluated for its wound healing efficacy using preclinical burn models. Hydroalcoholic extracts of the plant were formulated into topical creams (1% and 2.5%) and tested against silver sulfadiazine (1%) in Wistar rats with thermally induced partial-thickness burns. Phytochemical screening confirmed the presence of flavonoids, tannins, phenolics, saponins, and glycosides—compounds known for their antioxidant and anti-inflammatory properties. Over a 21-day treatment period, the 2.5% extract formulation significantly accelerated wound contraction, epithelialization, and skin restoration compared to controls and standard treatment (p < 0.0001). Histological and physical observations supported enhanced tissue regeneration and cosmetic recovery. These findings validate the traditional use of R. paniculatus in wound care and highlight its potential as a plant-based therapeutic for burn management